Pengaruh Kompetensi Digital Dan Gaya Kepemimpinan Terhadap Kinerja Karyawan Melalui Transformasi Digital (Studi pada Dinas Peternakan dan Kesehatan Hewan Provinsi Sumatera Barat) - Salsa Billa; Vicky Brama Kumbara; Andre Ilyas (Journal of Business Economics and Management | E-ISSN : 3063-8968, 2026)
This study aims to analyze the effect of digital competence and leadership style on employee performance through digital transformation as an intervening variable at the Department of Livestock and Animal Health of West Sumatra Province. A quantitative survey approach was employed. Data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 3.0. The results indicate that digital competence has a positive and significant effect on digital transformation (β = 0.502; t = 4.408; p < 0.05). Leadership style also positively and significantly influences digital transformation. Digital competence significantly affects employee performance. However, leadership style has a negative and insignificant effect on employee performance. Digital transformation does not mediate the relationship between digital competence or leadership style and employee performance. The R² value of employee performance is 0.816, indicating strong explanatory power. The findings suggest that strengthening digital competence directly improves public employee performance rather than relying on digital transformation mediation mechanisms.